TRACE ELEMENT COMPOSITIONS OF SUBMICROSCOPIC INCLUSIONS IN COATED DIAMOND: A TOOL FOR UNDERSTANDING DIAMOND PETROGENESIS - Tomlinson E.; Jones A.P.; Schrijver I.De.; Moens L.; Vanhaecke F.; Corte K.De. (My University, 2005)
Trace element compositions of submicroscopic inclusions in both the core and the coat of five coated diamonds from the Democratic Republic of Congo (DRC, formerly Zaire) have been analyzed by Laser Ablation Inductively Coupled Mass Plasma Spectrometry (LA-ICP-MS). Both the diamond core and coat inclusions show a general 2–4-fold enrichment in incompatible elements relative to major elements. This level of enrichment is unlikely to be explained by the entrapment of silicate mantle minerals (olivine, garnet, clinopyroxene, phlogopite) alone and thus submicroscopic fluid or glass inclusions are inferred in both the diamond coat and in the gem quality diamond core. The diamond core fluids have elevated High Field Strength Element (Ti, Ta, Zr, Nb) concentrations and are enriched in U relative to inclusions in the diamond coats and relative to chondrite. The core fluids are also moderately enriched in LILE (Ba, Sr, K). Therefore, we suggest that the diamond cores contain inclusions of silicate melt. However, the Ni content and Ni/Fe ratio of the trapped fluid are very high for a silicate melt in equilibrium with mantle minerals; high Ni and Co concentrations in the diamond cores are attributed to the presence of a sulfide phase coexisting with silicate melt in the diamond core inclusions. Inclusions in the diamond coat are enriched in LILE (U, Ba, Sr, K) and La over the diamond core fluids and to chondrite. The coats have incompatible element ratios similar to natural carbonatite (coat fluid: Na/Ba ≈0.66, La/Ta≈130). The coat fluid is also moderately enriched in HFSE (Ta, Nb, Zr) when normalized to chondritic Al. LILE and La enrichment is related to the presence of a carbonatitic fluid in the diamond coat inclusions, which is mixed with a HFSE-rich hydrous silicate fluid similar to that in the core. The composition of the coat fluid is consistent with a genetic link to group 1 kimberlite.